STRUKTUR POLA ALIH TUTUR PADA PERCAKAPAN ANAK-ANAK - Trahutami, Sriwahyu Istana (HUMANIKA, 2012)
This study finds that children follow a specific pattern in their daily communication. They know when to talk and when to be silent as a litener. They also avoid jumbled roles while communicating and pay attention to communicationi rules. The practice of turntaking among children is highly influenced by their culture within their environment. Giving answers, monopolizing conversations, cutting current speaker is not found among children who are taught early about communication norms. Eventhough most children follow adjacency pairs theoretically, many examples show that they don’t always do that. Keywords : turn taking, adjacency pairs, children communication pattern